2008
DOI: 10.1051/0004-6361:200809517
|View full text |Cite
|
Sign up to set email alerts
|

The low-mass YSO CB230-A: investigating the protostar and its jet with NIR spectroscopy and Spitzer observations

Abstract: Context. To investigate the earliest phases of star formation and study how newly-born stars interact with the surrounding medium, we performed a line and continuum survey at NIR and mm-wavelengths of a sample of relatively isolated Bok globules. Aims. We present a follow-up observational program of a star-forming site in the globule CB230. From narrow-band continuum observations of this site, we had discovered a bright [FeII] jet, which originates in the low-mass YSO CB230-A. We aim to investigate the physic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…These are separated by 10 and are aligned in the east-west direction (Launhardt 2001(Launhardt , 2004. The eastern object, IRS2, is not detected beyond 24 µm (Massi et al 2008;Launhardt et al 2013). Outflows.…”
Section: Cb230mentioning
confidence: 98%
See 1 more Smart Citation
“…These are separated by 10 and are aligned in the east-west direction (Launhardt 2001(Launhardt , 2004. The eastern object, IRS2, is not detected beyond 24 µm (Massi et al 2008;Launhardt et al 2013). Outflows.…”
Section: Cb230mentioning
confidence: 98%
“…The sample only contains low-mass Class 0 protostars, except for SVS13-A. The M env and L bol are from Massi et al (2008) for CB230, Launhardt et al (2013) for B335, Crimier et al (2010) for IRAS16293, Sadavoy et al (2014), Ladjelate et al (in prep. ), and Maury et al (in prep.…”
Section: Introductionmentioning
confidence: 99%
“…Near-infrared imaging previously detected a companion separated from IRS1 by ∼10 (3000 AU) to the east (Yun 1996); we refer to this companion as IRS2. IRS2 has been detected at wavelengths between 1.2 µm and 24 µm (Massi et al 2008), but is undetected in Herschel data at 100 µm (Launhardt et al 2013), SCUBA at 450 µm (Launhardt et al 2010), and OVRO 1.3 mm and 3.4 mm data Launhardt 2001). CB230 IRS1 is also classified as a Class 0/I source with L submm /L bol = 0.037 and T bol = 189 K (Launhardt et al 2013).…”
Section: Sourcesmentioning
confidence: 99%
“…They suggested that these facts point to inaccuracies in the theoretical transition probabilities available. Massi et al (2008) cautioned against the possibility that the discrepancy between ratios could arise from inaccuracies in the telluric absorption correction caused by the 1.257 µm line falling in the region of the 1 ∆ g absorption band of atmospheric O 2 . Giannini et al (2015a) tried determining the Einstein spontaneous emission rates of the three Fe + lines using X-shooter spectra of HH1, still finding a few cases of discrepancies between their determination and data from the literature.…”
Section: Introductionmentioning
confidence: 99%